Pronounced reduction of acquisition of conditioned eyeblink responses in young adults with focal cerebellar lesions impedes conclusions on the role of the cerebellum in extinction and savings. (May 2016) - Ernst, T.M.; Beyer, L.; Mueller, O.M.; Göricke, S.; Ladd, M.E.; Gerwig, M.; Timmann, D.
Abstract: Human cerebellar lesion studies provide good evidence that the cerebellum contributes to the acquisition of classically conditioned eyeblink responses (CRs). As yet, only one study used more advanced methods of lesion-symptom (or lesion-behavior) mapping to investigate which cerebellar areas are involved in CR acquisition in humans. Likewise, comparatively few studies investigated the contribution of the human cerebellum to CR extinction and savings. In this present study, young adults with focal cerebellar disease were tested. A subset of participants was expected to acquire enough conditioned responses to allow the investigation of extinction and saving effects. 19 participants with chronic surgical lesions of the cerebellum and 19 matched control subjects were tested. In all cerebellar subjects benign tumors of the cerebellum had been surgically removed. Eyeblink conditioning was performed using a standard short delay protocol. An initial unpaired control phase was followed by an acquisition phase, an extinction phase and a subsequent reacquisition phase. Structural 3T magnetic resonance images of the brain were acquired on the day of testing. Cerebellar lesions were normalized using methods optimized for the cerebellum. Subtraction analysis and Liebermeister tests were used to perform lesion-symptom mapping. As expected, CR acquisition was significantly reduced in cerebellar subjects compared to controls. Reduced CR acquisition was significantly more likely in participants with lesions of lobule VI and Crus I extending into Crus II (p<0.05, Liebermeister test). Cerebellar subjects could be subdivided into two groups: a smaller group (n=5) which showed acquisition, extinction and savings within the normal range; and a larger group (n=14) which did not show acquisition. In the latter, no conclusions on extinction or savings could be drawn. Previous findings were confirmed that circumscribed areas in lobule VI and Crus I are of major importance in CR acquisition. In addition, the present data suggest that if the critical regions of the cerebellar cortex are lesioned, the ability to acquire CRs is not only reduced but abolished. Subjects with lesions outside these critical areas, on the other hand show preserved acquisition, extinction and saving effects. As a consequence, studies in human subjects with cerebellar lesions do not allow drawing conclusions on CR extinction and savings. In light of the present findings, previous reports of reduced extinction in humans with circumscribed cerebellar disease need to be critically reevaluated. Highlights: Delay eyeblink conditioning in young human subjects with focal cerebellar lesions. Lobules VI and Crus I contribute to acquisition of conditioned eyeblinks (CR). Lesions in critical cerebellar cortical regions appear to abolish CR acquisition. Conclusions on CR extinction/savings are impeded in such cases.